2020
DOI: 10.1155/2020/5097823
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of the Molecular Mechanism of Late‐Stage Heterotopic Ossification

Abstract: Background. Heterotopic ossification (HO) is a common disease happened in soft tissues after injury. The present study utilized the bioinformatics method to analyze the HO samples in a mouse burn/tenotomy-induced HO model to identify the possible key points and treatment targets. Methods. The transcriptome profiles of GSE126118 were obtained from the Gene Expression Omnibus (GEO) database. The study was based on a mouse burn/tenotomy-induced HO model, and 2 tenotomy samples and 3 uninjured contralateral hindli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, this has not been reported in humans. Another recent bioinformatics study showed that HO-related DEGs are mainly associated with metabolic processes in a mouse burn/tenotomy-induced HO model ( 37 ), but this has not been reported in humans. ACTR2 and ACTR3 are components of the seven-subunit Arp2/3 complex, which plays a key role in generating branched actin filament networks during many different cellular processes ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this has not been reported in humans. Another recent bioinformatics study showed that HO-related DEGs are mainly associated with metabolic processes in a mouse burn/tenotomy-induced HO model ( 37 ), but this has not been reported in humans. ACTR2 and ACTR3 are components of the seven-subunit Arp2/3 complex, which plays a key role in generating branched actin filament networks during many different cellular processes ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the increased expression level of ribosomal proteins may indicate the initiation and formation of aberrant ectopic ossification. The previous bioinformatics analysis about the late stage heterotopic ossification and proteomic analysis of HO ​+ ​tissue samples also identified ribosomal proteins such as RPL17, RPS18 exhibit a higher expression and act as key proteins of the molecular mechanism of heterotopic ossification [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as many studies have progressed, large amounts of genetic information uploaded to public databases has not been effectively utilized (13). Related studies (14,15) only analyzed the expression and functional enrichment of OA differential genes, focusing more on the impact of OA risk analysis. However, few people have analyzed the differential genes in the prognosis of patients with OA and the construction of the risk prognosis model.…”
Section: Introductionmentioning
confidence: 99%